A dialogia no ensino de ciências: um estudo do desenvolvimento do discurso em sala de aula - Ana Carolina Araujo da Silva (2015)
This research aimed to identify and characterize the transitions between dialogic and authoritative discourses over two different sequences of lessons. The investigated sequences are: chemical reactions for a Brazilian middle school eighth year; and molecular kinetic model for a Brazilian high school first year. Used data collection instruments were recorded on video audio and field notes. We initially used, for data analysis, communicative approach and interactions patterns categories proposed by Mortimer and Scott (2002 and 2003). Methodological procedures comprehended the analysis of twenty-three classes recorded on video, in real time, using Videograph® software. From this program, we obtained the speaker category, types of activity, communicative approach and types of initiations time percentages. Communicative approach category was analyzed both in each class and as a whole. With communicative approach total percentage, we identified that both teachers began classes with the dialogic discourse that it was disappearing along the instructional sequence. From the selected data panoramic analysis, eight distributed along the sequence episodes were analyzed. In these eight episodes, we identified five turning points. Turning points are characterized by the transition from dialogic to authoritative discourse and vice versa, and this change is often marked by the teacher. We found that, in these episodes, teachers involved students through activities in dialogic spaces and finalized them with authoritative discourse. For dialogic and authoritative discourse characterization, we used some beforehand available categories (interaction patterns and types of initiation), adapted others (statement intents) and created another one (statements repercussion). This enabled an analysis that highlights different phases and characteristics of the two teachers discourses. In dialogic discourse characterization, we identified in one episode that it is in two phases: in the discourse opening and in the exploration of ideas. Also, it may be the presence of triadic IRE pattern. In the statement intents, we identified that, in dialogic discourse, the teacher creates a problem, selects and shares students ideas, explores them and encourages students participation. Authoritative discourse is present in two moments of an episode: in students ideas evaluation and in the discourse closure. The most identified interaction pattern was the IRE, and the statements intents were to explore and evaluate. Results indicate the two teachers create moments to the students for them to express their ideas. However, they are different regarding to the level of interaction that they established with the students. The teacher called Leila prioritizes the movement to have control over the discussions, involving students in a new concepts construction. The teacher called Paulo, on the other hand, redirects the discussion according to the students demand. Our data revealed that, for meaning making in classroom, there is a need to involve students in transitions which promote discursive dynamics between dialogic and authoritative discourses, demonstrating that teaching and learning involve discursive processes that are closely interconnected.